Analyse des caractéristiques morphologique des ovins cas de la race Ouled –Djellal. - BENMILOUD, Abdelmadjid (My University, 2024)
The objective of this dissertation is to study the morphological characteristics of the Ouled Djellal sheep breed, conducted at the Si Mourad farm. The Ouled Djellal breed, known for its robustness and adaptation to arid conditions, represents a valuable resource for sheep farming in Algeria. The primary aim of this study is to determine whether the sheep at the farm are of pure breed or result from crossbreeding, by comparing their morphological characteristics to the standard norms of the Ouled Djellal breed. To achieve this, we measured specific characteristics such as live weight, withers height, body length, and ear length of the sheep at the farm. The data obtained were then compared to the recognized morphological standards for the Ouled Djellal breed. Our results indicate significant divergences, suggesting that the animals studied are not of pure breed.
Keywords: sheep-Ouled Djellal-morphology-breed-pure